Kelakat and Cultural Identity in Marriage Rituals: A Maqasid Al-Shari’ah Approach in Loloan Timur Muslim Traditions - Hasani; Wulan Suci Rahmadani; M. Fijar Ishlahul Ummah (Indonesian Journal of Islamic Law, 2024)
This study aims to examine and analyze the phenomenon of the Kelakat tradition, which is still controversial because some parties prohibit it because it is contrary to Sharia and has implications for shirk. Kelakat is a tradition in marriage that is often carried out by the majority of the East Loloan village community. It is passed down from generation to generation and is believed to eliminate bad luck, and if the ritual is not carried out, it can cause problems for the bride and groom. This research uses a qualitative method with a case study approach in East Loloan village, the theory used with Maqasid Al-Shari’ah Jasser Auda. The result of this research is that the Kelakat tradition has become a habit that has been attached to the East Loloan community to make it survive amid Muslim communities in East Loloan village and does not conflict with Sharia law because there has been a revolution in its implementation so that it is under the objectives of Sharia.